Biotransformation of the Textile Dye Reactive Black 5 with Aspergillus niger and Analysis of Ligninolytic Enzyme Activity - Prawitasari, Diah Ayu; Kardena, Edwan (Bogor Agricultural University, Indonesia, 2026)
Removal of textile dye using biological processes is considered more cost-effective, generates no hazardous byproducts, and is ecologically friendly. This study analyzes the removal of the synthetic dye Reactive Black 5 (RB5) using the biological agent Aspergillus niger. The Treatment occurred in a 250 mL Erlenmeyer flask containing a mixture of dye solution. The preliminary research treatment involved varying dye concentrations, which were then analyzed by examining enzyme activity and fungal growth at different shaker rotations. The initial findings on concentration variation indicated that it was effectively removed up to approximately 90%. Further research determined that the highest concentration, 200 ppm, was used. The results obtained with rotation variations up to the sixth day were 95% for 100 rpm and 93% for 150 rpm. Dye removal utilizes laccase, lignin peroxidase (LiP), and manganese peroxidase (MnP) as degrading enzymes. The highest amount of enzyme activity was achieved at 100 rpm, corresponding to the most effective dye removal. The enzyme activity at the 100-rpm variation was observed for MnP (62.2 U/L), LiP (32.2 U/L), and laccase (16.6 U/L). The rapid growth of the Aspergillus niger fungus is associated with the biomass, which influences the biosorption mechanism. Biodegradation pathways indicate the cleavage of aromatic bonds, with toluene and propanoic acid identified as the final products.